Чемпионат Европы по футболу 2012 глазами польских и русских интернетчиков - Katarzyna Kuligowska (Studia Rossica Posnaniensia)
The author presents the response of Internet users to the incidents that occurred during Euro 2012. A sociolinguistic analysis of comments on the fights between Polish and Russian fans was carried out. Several aspects of the national stereotypes included in the analyzed internet opinions that had been published on the Internet were presented.